Developing a model of the impact of corporate sustainability on the performance of Small and Medium-sized Enterprises in Dak Lak province - the moderating role of leadership competence and the innovation process - Lê Thanh Hà; Nguyễn Xuân Anh; Bùi Thị Bích Thủy; Trương Văn Thảo; Trương Thị Tuyết (Tay Nguyen Journal of Sciences, 2025)
This study aims to develop a model that examines the impact of corporate sustainability on the performance of small and medium-sized enterprises (SMEs) in Dak Lak province, with leadership competence and the innovation process acting as moderating variables. A qualitative research approach is employed to synthesize foundational theories, consolidate conceptual frameworks, and construct a model tailored to the local context. The literature review indicates that, although the relationship between sustainability and firm performance has been extensively studied, most prior research has focused on large corporations or developed countries, leaving a gap in in-depth studies within SMEs in transitional economies such as Vietnam. In particular, the roles of moderating factors such as leadership competence and the innovation process remain underexplored. Theoretically, the study proposes a highly generalizable integrated model grounded in stakeholder theory, transformational leadership theory, and institutional theory. This approach expands understanding of the multi-dimensional impacts (economic, social, environmental) of sustainability on firm performance under the influence of internal organizational factors. Practically, the model offers SMEs in Dak Lak strategic insights into the importance of sustainable development, while emphasizing the role of leadership capacity and innovation as key moderating mechanisms in an increasingly volatile economic environment. The findings are expected to provide a valuable reference for managers in planning sustainable growth strategies and improving operational performance.